Compound Difference Anti-Synchronization between Hyper-Chaotic Systems of Fractional Order - Khan, A.; Jahanzaib, L. S.; -, Nasreen; Trikha, P.; Khan, T. (Journal of Scientific Research, 2020)
In this article, the compound difference anti-synchronization between fractional order hyper-chaotic systems have been studied. Numerical simulations have been performed using MATLAB to verify the theoretical results on fractional order Xling, Vanderpol, Rikitake and Rabinovich hyper-chaotic systems.